The college wage gap in 10 European countries: Evidence from two cohorts - Giorgio Brunello; Simona Comi; Claudio Lucifora (Fondazione Eni Enrico Mattei (FEEM), 2000)
We study the recent evolution of the college wage gap with a unique data set that covers 10 European countries and two cohorts of male employees from the early to mid 1980s to the mid to late 1990s.We find evidence of significant cross country differences in the level and dynamics of the gap. There is also evidence that both the level and the growth of the college wage gap significantly differ between cohorts. The estimated growth in the gap turns out to be negatively correlated to changes in relative supply and positively correlated both with the long run rate of productivity growth and with an index of between industry demand shocks. Institutional changes also matter, and we find that countries that have experienced declines in union density, in the centralization of the wage bargain and in employment protection measures have also had a faster growth in the college wage gap.
Keywords: J31; 330; College wage gap; growth of college wage gap; labour market institutions; Europe; Lohnstruktur; Bildungsertrag; Westeuropa; Kohortenanalyse